Improving Study Decisions at Private Universities: The Role of Family, Price, and University Image - Budaya, Indra; Liantifa, Melifia; Sarmigi, Elex; Lestari, Anggia Ayu (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThis study examines and analyses the role of family factors on prices and brands on student decisions to choose private universities to continue their studies. This study involved 500 students from various private universities in Jambi Province to serve as samples. The results showed that in the first model, price and brand influenced the decision to choose private universities (PTS) in Jambi province, and the magnitude of the effect was 63.9%. Price, Brand and Family in the second model significantly affect the Selection Decision of Private Universities (PTS) in Jambi Province, with the magnitude of the influence being 75.5%. In the third model, the family plays a role or can moderate the impact of price and brand on choosing private universities (PTS) in Jambi Province. Keywords:Lecture Decisions; Family; Price; Brand; Private College